1976
DOI: 10.1246/bcsj.49.3454
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal and Molecular Structure of Naphthanthrone

Abstract: The crystals of naphthanthrone(C19H10O) are orthorhombic, with the P212121 space group and these lattice constants: a=17.345(17), b=3.973(13), c=17.392(14) Å, and Z=4. The structure was solved by the Patterson method and refined by a block-diagonal least-squares program to give an R-value of 0.085 on the basis of the 897 observed reflections collected by Weissenberg photographs. The molecule is planar within the limits of experimental error and has an approximate symmetry of mm. The molecules are stacked face-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…40 (1)A [(I [7,8,1,2-defg]anthrone (Fujisawa et al, 1976) lies between the observed values for (I) and (II).…”
Section: C(6)-c(16)-c(14)supporting
confidence: 59%
See 1 more Smart Citation
“…40 (1)A [(I [7,8,1,2-defg]anthrone (Fujisawa et al, 1976) lies between the observed values for (I) and (II).…”
Section: C(6)-c(16)-c(14)supporting
confidence: 59%
“…In contrast, naphth [7,8,1,2-defg]anthrone (Fujisawa, Oonishi, Aoki & Iwashima, 1976) does not exhibit such a dimeric structure.…”
Section: C(6)-c(16)-c(14)mentioning
confidence: 96%
“…The synthesis and purification of NT were performed according to the previously reported procedure (1). As solvents we used methanol, ethanol, and their deuterated compounds, C 2 H 5 OD, CH 3 OD and CD 3 OD: non-deuterated solvents were purchased from Koso Chemical, Tokyo, Japan, and the deuterated ones from Wako Pure Chemical Industries, Osaka, Japan, and used without purification.…”
Section: Methodsmentioning
confidence: 99%
“…Naphthanthrone, 6H-benzo[cd]pyren-6-one, (NT) is a penta-cyclic mono ketone and synthesized by glycerol condensation of pyrene (1). Its separation and purification are, however, so laborious that only a few studies of its spectroscopic properties exist in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neither the expected conventional McMurry reaction products, ( E )- and ( Z )-7-(7 H -benz[ de ]anthracenylidene)-7 H -benz[ de ]anthracene (( E )- 7 and ( Z )- 7 ), nor their electrocyclization−aromatization C 34 H 16 products, dibenzo[ fg , ij ]phenanthro[2,1,10,9,8,7- pqrstuv ]pentaphene ( 8 ) and perylo[3,2,1,12- pqrab ]perylene ( 9 ), were found in the reaction mixture. An analogous low-valent titanium-induced reductive “dimerization” of 4 afforded the overcrowded chiral LPAH dibenzo[ jk , uv ]dinaphtho[2,1,8,7- defg ;2‘,1‘,8‘,7‘- opqr ]pentacene ( 10 ) in 1.3% yield. The major product of the reaction was 6 H -benzo[ cd ]pyrene 25 (37% yield).…”
mentioning
confidence: 99%